Diane Dufresne en spectacle : I'impact de la gestualité - Chénier, Marie-Claude (Université de Montréal, 1988)
Keywords: Pas de lien web

Music consumption among English speaking teenage girls in the city of Montreal - Giles, Jennifer (Université Carleton, 1987)
Music Consumption among English Speaking Teenage Girls in the City of Montreal

Exposition au monastère des Ursulines de Québec - Grégoire-Reid, Claire; Vézina-Demers, Micheline (Les Cahiers de l'ARMuQ, 1987)

Muséalogue : Maryvonne Kendergi - Bail Milot, Louise (1985)
Muséalogue : Maryvonne Kendergi